Idealitas eksistensi hakim komisaris terhadap konstruksi peradilan di Indonesia - Bambang Satriya; Abdul Wahid; Mirin Primudyastutie (University of Merdeka Malang, 2021)
This study aims to describe one of the political efforts of legal reform in the field of justice in Indonesia. This research describes that the presence or existence of norms that look at commissioner judges in preliminary examinations is part of an effort to prevent the possibility of the practice of abuse of roles or authorities that can damage the building of the criminal justice system with the modus operandi of violating the rights of suspects, whose role is more specific and has a value of certainty. compared to the role of judges in pretrial as it is today. This type of research in the problem of commissioner judges related to the ideals of legal reform is classified as normative juridical research or doctrinal research. The result obtained is that the existence of this commissioner judge is idealized to have a major impact on the reform of the performance model carried out by law enforcement officers at the fundamental level (investigation and investigation). The pattern of